Knowledge, attitude and preventive practice of women concerning osteoporosis above 45 years women - Agarwal, Juhi; Badkur, Poorva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective is to determine the knowledge, attitude and preventive practice of women above 45 years old. Methods: It is a cross-sectional analytical study of 100 women above 45 years of upper class women. The interview schedule consisted of 4 parts including questions about knowledge, attitude and practice (KAP) and also demographic questions. Results: A significant relationship between the score of preventive practice and all the following parameters was found: level of education, hearing about osteoporosis, knowledge score, perceived barrier to preventive actions and perceived seriousness of osteoporosis. Conclusions: Inaccurate or insufficient knowledge and their negative attitude to the preventive actions and their weak practice in case of prevention, it is the responsibility of health policymakers and medical associations to plan for osteoporosis education and prevention initiatives.